Mechanizmy i strategie konstruowania języka w dystopii Władimira Sorokina Dzień oprycznika - Zywert, Aleksandra (Studia Rossica Posnaniensia, 2025)
The novel Day of the oprichnik (День опричника), written in 2006, perfectly fits into the contemporary concept of dystopia as a literary genre - it reflects the fears of the modern world and responds instantly to all its social and political problems. Initially, the work was rather cautiously received by critics, but today it is considered a classically prophetic text. It turns out that Sorokin had predicted the direction of today's Russia already 15 years earlier. The action takes place in 2027 in Moscow, the plot is straightforward, and the structure clearly refers to One day in the life of Ivan Denisovich (Один день Ивана Денисовича, 1962) by Alexander Solzhenitsyn. The study of dystopia is carried out through the language of the created reality. Sorokin uses (not for the first time) the strategy of modelling the language of the future through layering - here it is a hybrid of modern Russian language, archaic from the era of Ivan the Terrible, and among others, Chinese. As a result, the text, according to the author's intention, transforms into a parodic-schizophrenic-satirical metaphor of contemporary Russia - a state perpetually "frozen" in the past, without any prospects for "healing".